Synthesis and Crystal Structure of Two Polydimensional Molecular Architectures from Cobalt(II), Copper(II) Complexes of 2,4-Diamino-6-pyridyl-1,3,5-triazine - Li1, Jia-Yan; Xie2, Ming-Jin; Jiang3, Jing; Chang3, Qiao-Wen; Ye3, Qing-Song; Liu3, Wei-Ping; Chen3, Jia-Lin; Ning1, Ping (Asian Journal of Chemistry, 2014)
Two new Co(II) and Cu(II) complexes of 2,4-diamino-6-pyridyl-1,3,5-triazine (ptzda) have been synthesized and structurally characterized. Crystal structure studies reveal that Co atom is six-coordinated by four nitrogen atoms from four dicyanamide anions and the other two nitrogen atoms from 2,4-diamino-6-pyridyl-1,3,5-triazine and each cobalt atom are connected by two [N(CN)2]– anions to form an infinite double-stranded bridge fashion to give 2D ladder-like motifs. Whereas, Cu atom is five-coordinated by two nitrogen atoms from two dicyanamide anions and the other two nitrogen atoms from 2,4-diamino-6-pyridyl-1,3,5-triazine and each copper atom is connected by one methanol to form an infinite double-stranded bridge fashion to give 1D ladder-like motifs.